The notebooks of Sonny Rollins - Rollins, Sonny (New York Review Books, 2024)
Sonny Rollins is one of the greated American musicians, whose live improvisations are legendary. In 1959, he took a step back from performing and recording to invest himself in musical exploration. This was also when he started the notebook in which he recorded his pondering on art and life and his search for meaning in words and in images. "The Notebooks of Sonny Rollins" provides an unequaled glimpse into the mind and workshop of this musical titan, as well as a weath of insight and inspiration to readers --